The Role of the Ventromedial Prefrontal Cortex in Purchase Intent Among Older Adults - Koestner, Bryan P.; Hedgcock, William; Halfmann, Kameko; Denburg, Natalie L. (Frontiers in Aging Neuroscience, 2016)
Older adults are frequently the targets of scams and deception, with millions of individuals being affected each year in the United States alone. Previous research has shown that the ventromedial prefrontal cortex may play a role in vulnerability to fraud. The current study examined brain activation patterns in relation to susceptibility to scams and fraud using functional magnetic resonance imaging. Twenty-eight healthy, community-dwelling older adults were subdivided into groups of impaired and unimpaired decision makers as determined by their performance on the Iowa Gambling Task. While in the scanner, the participants viewed advertisements that were created directly from cases deemed deceptive by the Federal Trade Commission. We then obtained behavioral measures involving comprehension of claims and purchase intentions of the product in each advertisement. Contrasts show brain activity in the ventromedial prefrontal cortex was less correlated with purchase intention in impaired versus unimpaired older adult decision makers. Our results have important implications for both future research and recognizing the possible causes of fraud susceptibility among older adults.